The Association of Metabolic Syndrome and Urolithiasis - Yee V. Wong; Paul Cook; Bhaskar K. Somani (International Journal of Endocrinology)
There has been an increasing prevalence of kidney stones over the last 2 decades worldwide. Many studies have indicated a possible association between metabolic syndrome and kidney stone disease, particularly in overweight and obese patients. Many different definitions of metabolic syndrome have been suggested by various organizations, although the definition by the International Diabetes Federation (IDF) is universally considered as the most acceptable definition. The IDF definition revolves around 4 core components: obesity, dyslipidemia, hypertension, and diabetes mellitus. Several hypotheses have been proposed to explain the pathophysiology of urolithiasis resulting from metabolic syndrome, amongst which are the insulin resistance and Randall’s plaque hypothesis. Similarly the pathophysiology of calcium and uric acid stone formation has been investigated to determine a connection between the two conditions. Studies have found many factors contributing to urolithiasis in patients suffering from metabolic syndrome, out of which obesity, overweight, and sedentary lifestyles have been identified as major etiological factors. Primary and secondary prevention methods therefore tend to revolve mainly around lifestyle improvements, including dietary and other preventive measures.